Electrochemical Difunctionalization of Alkenes by a Four‐Component Reaction Cascade Mumm Rearrangement: Rapid Access to Functionalized Imides. Issue 9 (21st January 2020) - Zhang, Xiaofeng; Cui, Ting; Zhao, Xin; Liu, Ping; Sun, Peipei
Abstract: An electrochemical four‐component reaction cascade Mumm rearrangement was developed. It is a rare example of in situ generation of O‐acyl isoamides for 1, 3‐(O→N) acyl transfer. Inexpensive, commercially available arylethylenes, aryl or heterocyclic acids, acetonitrile, and alcohols were used as substrates. A wide range of aryl acids and alcohols were tolerated and provided imides in satisfactory yields. Subsequent hydrolysis of imides could be utilized to synthesize valuable amides and β‐amino alcohol derivatives. Abstract : Collect four : A four‐component reaction based on arylethylenes, aryl acids, acetonitrile, and alcohols has been designed that enables the difunctionalization of alkenes and the formation of imides under electrochemical conditions. Mechanistic studies support a 1, 3‐(O→N) acyl transfer of O ‐acyl isoamides via Mumm rearrangement.